Complex Left Atrial Appendage Morphology Is an Independent Risk Factor for Cryptogenic Ischemic Stroke - Basu-Ray, Indranill; Sudhakar, Deepthi; Schwing, Gregory; Monlezun, Dominique; Zhang, Lucy; Shah, Sumit K.; Pujara, Deep; Ting, Kevin; Rafeh, Nidal Abi; Ali, Gholam; Cassidy, Mark; Ellenbogen, Kenneth; et al. (Frontiers in Cardiovascular Medicine, 2018)
Importance: Ischemic strokes pose a significant health burden. However, the etiology of between 20 to 40% of these events remains unknown. Left atrial appendage morphology may influence the occurrence of thromboembolic events. Design: A retrospective cross-sectional study was conducted to investigate the role of LAA morphology in patients with atrial fibrillation (AF) and cardioembolic-associated stroke and patients with cryptogenic stroke without atrial fibrillation. LAA morphology is classified into two groups: 1) simple (chicken-wing) versus 2) complex (non-chicken wing) based on transesophageal echocardiography (TEE) findings. In addition to the LAA morphology, left atrial parameters, including orifice diameter, depth, emptying velocity, and filling velocity, were collected for both groups. Mathematical, computational models were constructed to investigate flow velocities in chicken-wing and non-chicken wing morphological patterns to assess LAA function further. Findings: TEE values for volume, size, emptying, and filling velocities were similar between simple and complex LAA morphology groups. Patients with cryptogenic stroke without co-existing AF were noted to have significantly higher rates of complex LAA morphology. Chicken-wing LAA morphology was associated with four-fold higher flow rate (kg/s) in computational simulations. Conclusions: Complex LAA morphology may be an independent contributing factor for cryptogenic strokes. Further studies are warranted to investigate the mechanism involved in LAA morphology and thromboembolic events.